God or Self? The Re-Emergence of God in the Unconscious - Rico Sneller (Religions, 2023)
Toward the end of the Age of Enlightenment, rationalism’s demise gradually entailed the transcendent God’s demise. In this article, I will draw on the resurfacing of God in the ensuing tradition of the unconscious. Whereas philosophers such as Schopenhauer or Eduard von Hartmann, undermining the alleged rational consciousness, assumed the existence of an impersonal, unconscious, yet collective will, others took one step back and maintained a higher yet individual “consciousness” beyond the threshold of sense perception. I am referring to the philosopher–spiritualist Carl du Prel (1833–1899), whose notion of a personal unconscious inaugurated both Freud’s and Jung’s “psychologies” of the unconscious. In many respects, Du Prel’s “personal unconscious” (“transcendental consciousness”) interestingly corresponds to the traditional conception of God; it is morally binding and has a cosmological impact. I will explore to what extent Carl du Prel, in his philosophy of the unconscious, allows for a re-emergence of God in the form of a personal unconscious. I will also try to specify the conditions of possibility for equating these unruly notions (“God” and “unconscious”). My question will be as follows: can we consider the personal unconscious (or transcendental consciousness), as developed in Carl du Prel’s work, as a re-emergence of a more traditional conception of a transcendent God in terms of reason and intelligibility?